Zinc Oxide and Tea Theaflavin Suppress Enterotoxigenic Salmonella Isolated From Swine Livestock. (14th June 2022) - Jackson, Steven; Andrews, Kathleen; Banz, William; Phillips, Timothy; Harvey, Roger
Abstract: Objectives: Salmonella infection can lead to diarrhea and diminished weight gains in livestock, as well as gastroenteritis in humans. Although antibiotics have been used historically on the farm to promote animal growth, this practice may also foster development of resistant bacterial strains and thereby deplete our arsenal of effective antibiotic therapies. Here, Salmonella typhimurium (isolated from cecal contents of swine) is shown to be vulnerable to zinc oxide (ZnO) and theaflavin 3, 3'-digallate (TF3), each at gastrointestinal concentrations achievable via the diet. Methods: Propagation of Salmonella in Mueller-Hinton broth suspension was assessed in dose-response experiments involving ZnO or TF3 exposures, and subsequently in experiments using a combination of these compounds. Results: The minimum effective concentrations against 6-hour growth of Salmonella at 37°C were 1 mM ZnO (62% inhibition) or 25 μM TF3 (30% inhibition). Salmonella growth was inhibited up to 99.6% when exposed to 7 mM ZnO, and up to 89% when exposed to 100 μM TF3. In concurrent experiments assessing individual effects of either ZnO or TF3, as well as a combination of these treatments, the minimum effective concentration of ZnO was found to be more potent given alone than when given in combination with TF3. Conclusions: These findings suggest that physiological concentrations of ZnO within the human gut lumen (upon consuming dietary supplements containing less than the Tolerable Upper Intake Level) may limit or prevent the ability of Salmonella to propagate. Similarly, TF3 (at human gut concentrations upon consuming less than a single cup of black tea) appears to suppress Salmonella, yet TF3 could compete or otherwise constrain the efficacy of ZnO. Applications of these findings may include customized ZnO or TF3 delivery platforms for use in humans at high risk of diarrheal disease or other gastrointestinal disorders (e.g., military personnel on deployment under austere environmental conditions), as well as in agricultural practices to support animal welfare and normal growth without need for therapeutic antibiotics. Funding Sources: Supported by USDA and Texas A&M AgriLife Research.